New norms and opportunities from the COVID-19 pandemic crisis in a higher education setting: perspectives from Universiti Brunei Darussalam. Issue 3 (20th January 2021) - Shahrill, Masitah; Petra, Mohamad Iskandar; Naing, Lin; Yacob, Joanna; Santos, Jose H.; Abdul Aziz, Anita B.Z.
Abstract : Purpose: This paper aims to share how it was possible to change the way business was conducted in a short period in order to continue the academic semester and seek alternatives to manage the day-to-day university affairs in the midst of a pandemic crisis at a higher education setting. As a result, the authors' experiences have created new norms and opportunities for the university. Design/methodology/approach: The coronavirus disease 2019 (COVID-19) pandemic in Brunei Darussalam is an evolving situation with extraordinary challenges for staff and students of the university. Although the campus remains open and essential services were continuously provided, the university had to implement and adapt to new norms instinctively to minimise the potential pathways for community spread of the coronavirus and at the same time minimise interruption in teaching and learning. Findings: Firstly, structured blended learning will be the basis of teaching and learning, alongside ensuring the highest quality of online education and successful achievement of the intended learning objectives. Secondly, blended learning will open more opportunities to offer programmes in a more flexible, personalised, student-centric and lifelong learning manner, with the option of taking a study hiatus at students' convenience. Thirdly, there will be more global classrooms and the exchange of online modules with international partner universities. Fourthly, short programmes such as the Global Discovery Programmes will be modified and improvised to become an online learning experience. And finally, there will also be the opportunity to understand and consider the physical and mental well-being and durability of the university community in overcoming a national crisis situation. Originality/value: This paper is intended to be a conceptual paper where the authors describe novel experiences during the pandemic. The authors' views, interventions and experiences may result into a new model for higher education that will reposition students to the new global markets and economy.